METHODS OF PSYCHOSOCIAL REHABILITATION IN PSYCHIATRIC INSTITUTIONS OF THE ORYOL REGION AT THE MODERN STAGE OF ORGANIZATION OF PSYCHIATRIC CARE - G. R. Gardanova; M. A. Nekrasov; D. F. Khritinin; D. N. Chernov (Исследования и практика в медицине, 2016)
The article considers actual issues of psychosocial rehabilitation at the present stage of psychiatric care to the population of the Oryol region.The purpose. Study and generalize the experience of the use of methods of psychosocial rehabilitation in several psychiatric institutions of the Oryol region.Materials and methods. 1. The analysis of activity of out-patient departments, where we developed a new "development Program of sociorehabilitation service in regional psychoneurologic dispensary". 2. Analysis of the activity of hospital services, where the main role is played by psycho-social rehabilitation. 3. The analysis of new forms of psychosocial rehabilitation: in terms of the specifics of Oryol oblast psychiatric hospital of specialized type with intensive supervision (OPHSTIO).Results. As a result of the analysis we identified the most effective methods of sociorehabilitation: outpatient: "Social card of the outpatient" is intended for persons in need of social, psychological, legal and other professional assistance, that allows to plan and control the types of assistance provided. The organization of a hostel for patients at the outpatient stage, which allowed to introduce a "full" recovery cycle. In OPHSTIO — implementation of multiprofessional teams and "sick tips" and the opening of an Orthodox chapel of the Mother of God icon "All grieving pleasures".Conclusions. Methods of psychosocial rehabilitation allowed to optimize the work of the main stages of treatment and rehabilitation processes, to provide in a timely manner the necessary comprehensive care to patients based on individual needs of the mentally ill in the outpatient and inpatient therapy in the Oryol region.